Determinants of renewable energy and their impact on economic growth - Tee, Wu Shun (2020)
Renewable Energy has gained significant popularity in recent years as a result of the concerns toward climate change and the debate over the limited supply by traditional energy resources such as coal, oil and gas. It has been argued that sustainable energy supply associated with the promotion of clean energy could serve as an important engine for growth. Intuitively, sounds protection reinforce the investment in the renewable energy sector due to the renewables investor might feel more confidence toward their efforts being recognized. The first objective of this study carried out in attempt to examine if intellectual property right is an important driver for the renewable energy production. By employing dynamic panel Generalised Method of Moments (GMM) from 1986 – 2014 which covers the sample 59 countries. The empirical results show that there is strong evidence to conclude that intellectual property rights indeed an important driver for the renewable energy electricity production. Greater protection right motivates the renewables energy firm to increase the energy production from renewable resources. Our findings further suggest that stronger protection tends to propagate the deployment of renewable energy technologies which ultimately promote the renewable energy production. Tremendous surge in the oil price drawn the attention to the renewable energy consumption recent years due to the spike in oil price might be the stimulus engine for renewables consumption. Throughout the application of dynamic panel threshold methodology in investigating the impact of oil prices on renewable energy consumption growth by using a range of data from 1995 to 2018 that consisted of 160 countries, which were divided into; high-income, upper-middle-income, lower-middle-income and low-income groups. The empirical results, based on a nonlinear framework, indicated that there is an oil prices threshold to renewable energy consumption. The results reveal that above the threshold, oil prices are negatively and significantly related to growth in renewable energy consumption. The result of high-income group also demonstrated that oil prices have a negative and statistically significant impact on renewable energy consumption growth during times of high oil prices. Nevertheless, for the upper-middle income group, oil prices is a positive and significant determinant of renewable energy consumption growth below the threshold level. The lower-middle-income group indicated that the impact of oil prices is insignificant during times of low and high oil prices. The low-income group showed that the impact of oil prices is weak significant, below the threshold level. Our findings further suggest that there is no substitution effect between oil prices and renewable energy, but rather, that both complemented each other. Any increase in oil prices will harm growth in renewable energy, as oil continues to be an important production input in the renewable energy sector. Continuously targeting the renewable energy consumption raise an awareness of the environmentally friendly energy which ultimately could trigger a change in the energy trend for future generation. Financial assistance is critically important to support the renewable energy consumption particularly due to the cost of acquiring the renewable energy is relatively higher compared to conventional energy. Therefore, with respect to the concern raised on whether finance does impose any impact to the renewable energy consumption and subsequently growth, the third objective of this study aim to examine the moderating impact of finance on renewable energy to growth. By applying panel GMM methodology with a set of data for 106 countries ranging from 2006 to 201, this study found that country with well-developed financial system tends to promote the economic growth while country with least developed financial system will affect economic growth negatively. These findings imply that renewable energy consumption will spur the growth but only in the present of strictly regulated financial framework. Our findings suggest that countries with well-developed financial system might have the possibility to avoid from the problem with asymmetric information which eventually could further reduce the potentially losses of lenders, thus, they will be willing to lend more for the renewables borrowers. On the other hand, countries with least-developed financial system might conceal some information keen to be known by lenders which in turn might dampen the renewable energy industry due to the users will find it difficult to get the financial resources.